Predictive factors associated with radiation dermatitis in breast cancer. (2021) - Behroozian, Tara; Milton, Lauren; Li, Nim; Zhang, Liying; Lou, Julia; Karam, Irene; Wronski, Matt; McKenzie, Erin; Mawdsley, Gord; Razvi, Yasmeen; Chow, Edward; Ruschin, Mark
Highlights: Demographic and treatment characteristics were found to increase patients' susceptibility to developing radiation dermatitis. The administration of a boost was predictive of erythema, edema, and desquamation. Predictors of erythema included a high dose fractionation or tissue volume irradiated. Higher pain was reported among patients with a high body mass index or dose fractionation schedule. The findings of this prospective study may inform future practice on the care and prevention of skin toxicities in high-risk patients. Abstract: Purpose: Radiation dermatitis (RD) is a side effect that frequently arises during radiotherapy (RT) in breast cancer patients. The present study investigates possible predictive factors of RD, as well as the use of skin treatments to manage symptoms. Methods: Demographic and treatment characteristics were collected retrospectively, while skin symptoms and treatments were collected prospectively for patients who received adjuvant RT between December 2013 and November 2015. Patients were seen weekly by clinicians throughout treatment, during which a clinician-reported survey was completed on RD symptoms and skin treatments. Possible predictive factors were correlated with skin outcomes through a univariate ordinal logistic regression analysis. Results: A total of 1093 patients were included in this analysis. Predictive factors for erythema included dose fractionation ( p <0.0001), tissue volume irradiated by tangential fields ( p = 0.01), and administration of a boost ( p = 0.005). High BMI (≥30 kg/m 2 ) ( p = 0.0004) and boost ( p = 0.02) were predictive of edema. A dose of 50 Gy/25 ( p <0.0001) and a high irradiated tissue volume ( p = 0.0001) were predictive of desquamation. A dose of 50 Gy/25 ( p = 0.0005) and high BMI ( p = 0.02) were predictors of pain. Bolus use was the only factor associated with bleeding ( p = 0.02). Patients who developed desquamation were likely to receive corticosteroids/antihistamines ( p <0.0001), topical antibiotics/antifungals ( p <0.001), and dressings ( p <0.0001). Conclusion: The findings of this study provide evidence of potential predictors of RD and methods of symptom management based on symptom severity. Prevention of RD is needed among high-risk groups, such as patients with a high BMI or receiving a standard fractionation, boost, or bolus.